PENGARUH SISTEM KENAIKAN PANGKAT TERHADAP MOTIVASI KERJA PEGAWAI NEGERI SIPIL DI KANTOR PERTANAHAN KOTA SORONG - Lena, Rolin j; Dengo, Salmin; Ruru, Joorie Marhaen (Sam Ratulangi University, 2016)
Abstract: Rank Promotion is an award given on work performance and dedication of civil servants of theState. Rank Promotion is the driving motivation for civil servants to further enhance the devotion incarrying out the task. This study was to determine the effect of the promotion system of work motivationoffice employee city land sliding.The method used in this research is quantitative method. Data and information collected throughquestionnaire techniques and equipped with observation techniques, source data / research respondents areall employees of the office of city land sliding as much as 24 people. The analysis technique used by a tableof frequency hypothesis testing, product moment correlation and simple linear regression.Based on the analysis, it is known that: the results of the analysis of the technique of analysis table (tableof frequency) note that the distribution of respondents to variable promotions that are in the category of